ANESTHETIC MANAGEMENT OF HUGE MULTINODULAR GOITER WITH COMPROMISED AIRWAY - Ahmed, Saleem; Zaeem, Khalid; Kashif, Sanum; Uddin, Syed Samee (Pakistan Armed Forces Medical Journal, 2020)
A 52 years old woman with MNG, came for thyroidectomy. Goiter was huge, causing tracheal compression, narrowing and deviation to the left. For induction of general anesthesia (GA), awake intubation with 6.5mm ID (Internal diameter), armoured endotracheal tube (ETT) was performed with the help of flexible fiber-optic bronchoscope (FOB).